Metajournalistic Discourse and Reporting Policies on White Nationalism - Perreault, Gregory; Meltzer, Kimberly (The Journal of communication inquiry, 2024)
In 2016 and 2017, several newsrooms presented guidelines for using the term “alt-right” in the wake of events such as the Unite the Right rally in Charlottesville, Virginia (USA) and the US presidential campaign of Donald Trump. This study analyzed metajournalistic discourse regarding the use of the term “alt-right” including internal newsroom policies and updates to newsroom manuals and externally published public discourse. The analysis tracks how news organizations and academic and trade journalism associations participated in discourse about the use of “alt-right,” and their peers’ policies around use of the term. The study finds that discourse shifted from requiring contextualization of the term in the first wave to requiring journalists to define the term or not use it at all in the second wave that began with the Charlottesville rally. Journalism organizations acknowledged, at times endorsed, and used each other's statements in developing their own understandings as an interpretive community and a community of practice.